COMPARATIVE STUDY OF INFORMAL BUSINESS ENTERPRISES IN BATURAJA - Harby R. Wiralaga (STIE DWI SAKTI BATURAJA, 2018)
The purpose of this study is to compare informal business enterprises in Baturaja on the basis of vending location, by highlighting on start-up capital, working capital, labor employment, operating hours, and operating income. The outcome is to generate contribution for local government of Ogan Komering Ulu Regency to initiate policy in organizing and empowering informal economy sector. The research applied descriptive method, and the sampling method applied is area sampling, a method of sampling used when no complete frame of reference is available. The primary data is collected by observation and structured interview. A large portion of informal business enterprises run by women, whereas the rest by men. Informal entrepreneurs and street vendors in Baturaja are educated workforce, and tribal origins are dominated by Oganese (native) and Javanese (non-native). Informal business enterprises in five vending location have distinctive characteristics, but they have three characteristics in common, i.e. labor employment size, lucrative vending location, and do not perceive any benefit and advantage of formality. Policy to formalize the informality in Baturaja, and OKU Regency at large can be systematically done by considering these five key elements simultaneously, i.e. relocating, licensing, taxing, facilitating, and protecting.